Surgeons' and trainees' perceived self‐efficacy in operating theatre non‐technical skills. Issue 6 (19th March 2015) - Pena, G.; Altree, M.; Field, J.; Thomas, M. J. W.; Hewett, P.; Babidge, W.; Maddern, G. J.
<x xml:space="preserve">Abstract</x> Background An important factor that may influence an individual's performance is self‐efficacy, a personal judgement of capability to perform a particular task successfully. This prospective study explored newly qualified surgeons' and surgical trainees' self‐efficacy in non‐technical skills compared with their non‐technical skills performance in simulated scenarios. Methods Participants undertook surgical scenarios challenging non‐technical skills in two simulation sessions 6 weeks apart. Some participants attended a non‐technical skills workshop between sessions. Participants completed pretraining and post‐training surveys about their perceived self‐efficacy in non‐technical skills, which were analysed and compared with their performance in surgical scenarios in two simulation sessions. Change in performance between sessions was compared with any change in participants' perceived self‐efficacy. Results There were 40 participants in all, 17 of whom attended the non‐technical skills workshop. There was no significant difference in participants' self‐efficacy regarding non‐technical skills from the pretraining to the post‐training survey. However, there was a tendency for participants with the highest reported self‐efficacy to adjust their score downwards after training and for participants with the lowest self‐efficacy to adjust their score upwards. Although there was significant improvement in non‐technical skills performance from the first to second simulation sessions, a correlation between participants' self‐efficacy and performance in scenarios in any of the comparisons was not found. Conclusion The results suggest that new surgeons and surgical trainees have poor insight into their non‐technical skills. Although it was not possible to correlate participants' self‐belief in their abilities directly with their performance in a simulation, in general they became more critical in appraisal of their abilities as a result of the intervention.